2015
DOI: 10.37831/jik.v2i2.8
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH TERAPI MUSIK TERHADAP PENURUNAN TINGKAT KECEMASAN PADA ANAK YANG DIRAWAT DI RUMAH SAKIT Dr.OEN SURAKARTA

Abstract: Background. Hospitalization is a process that for some reason or emergency plans, so the children had to be hospitalized can cause children to experience anxiety. To overcome anxiety management can be given psychotherapy, one of which is with music therapy. Based on the data obtained through patient registration book entry of data obtained that the number of pediatric patients aged 3-6 years who were admitted to Teratai Ward. Dr. Oen Surakarta in September amounted to 43 children, with the number 5 top disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…The pre-test score is a value that indicates the subject's initial ability before being given treatment. While the post test is a value that shows an increase or decrease in the dependent variable after being given treatment (Seniati, 2011). Therefore, it can be concluded that if there is a difference in the pre-test and post-test scores, where the post-test score is significantly higher, it can be said that murottal Al-Qur'an therapy is effective in increasing learning concentration.…”
Section: Methodsmentioning
confidence: 99%
“…The pre-test score is a value that indicates the subject's initial ability before being given treatment. While the post test is a value that shows an increase or decrease in the dependent variable after being given treatment (Seniati, 2011). Therefore, it can be concluded that if there is a difference in the pre-test and post-test scores, where the post-test score is significantly higher, it can be said that murottal Al-Qur'an therapy is effective in increasing learning concentration.…”
Section: Methodsmentioning
confidence: 99%
“…Musik sangat baik dalam mempengaruhi perasaan atau emosional seseorang sehingga menciptakan suasana yang lebih nyaman dan memberikan rasa bahagia (Nurjatmika, 2012). Kaitan yang erat antara musik dan kesehatan sudah tidak diragukan lagi, bahwa seorang individu akan terbawa ke dalam suasana hati yang baik dalam waktu singkat saat mendengarkan musik kesukaannya (Setyaningsih, Aminingsih, & Hastari, 2014).…”
Section: Pendahuluanunclassified